1985
DOI: 10.3382/ps.0640529
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Nutritive Value of Naked Oats (Avena nuda L.) in Broiler Diets

Abstract: Two experiments were conducted using broiler chicks to evaluate naked oats (Avena nuda L.) as a potential feed ingredient. Experiment 1 was designed to provide the chemical composition of naked oats (NO) and assess its metabolizable energy. Naked oats contained a low concentration of avenin and was superior to corn with respect to the amino acid profile and mineral content. The total lipid content of NO (6.85%) with 30.9% linoleic acid was higher than that of most cereal grains and contributed to a relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…(Cave et al 1990). Thus the present conclusion as to the utility of naked oat in the broiler starter diet differs from those of Guillaume and Cabet (19'73) and Maurice et al (1985) who reported detrimental effects on growth. Hulan et al (1981) (Friend et al 1988) and of the lower bio-availability of lipids, associated with the ingestion of oat gum (Cave et al 1990).…”
Section: Methodscontrasting
confidence: 56%
“…(Cave et al 1990). Thus the present conclusion as to the utility of naked oat in the broiler starter diet differs from those of Guillaume and Cabet (19'73) and Maurice et al (1985) who reported detrimental effects on growth. Hulan et al (1981) (Friend et al 1988) and of the lower bio-availability of lipids, associated with the ingestion of oat gum (Cave et al 1990).…”
Section: Methodscontrasting
confidence: 56%
“…The data, as presented, span the growing and finishing periods because no effects of level of dietary naked oats were apparent within either of these periods. The lack of differences among the dietary treatments parallels the results ofprevious broiler studies regarding the variables of body weight (Maurice et al 1985), weight gain (Cave and Burrows 1985) and feed efficiency (Maurice et al 1985).…”
mentioning
confidence: 55%
“…Cave et al (1990) reported that treatment with the enzyme p-glucanase reduced the effect ofB-glucan on growth, confirming the adverse effect of this polysaccharide. Maurice et al (1985) reported that 60% naked oats in broiler diets reduced bone strength and increased the incidence of leg deformities at 7 wk of age. These detrimental effects of naked oats were considered to be due to a phosphorus deficiency caused by a relatively high phytic acid content in the diet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A broiler feeding trial carried out by Maurice et al (1985) concluded that naked oats could constitute up to 400 g kg −1 of dietary intake without adverse effects on meat quality and production. A study of laying hens demonstrated that egg yields and feed utilization were equal where hulless oats were substituted for corn and soy, though at a high proportion (600 g kg ) of dietary intake, oats were associated with a 4-day delay in sexual maturity (Cave et al, 1989).…”
Section: Introductionmentioning
confidence: 99%